Identification and Validation of a Novel Antibacterial Compound MZ-01 against Methicillin-Resistant Staphylococcus aureus - Junshu Yang; Christopher Brown; Wayland Noland; Timothy J. Johnson; Yinduo Ji (MDPI AG, 2022)
The discovery of new classes of antibiotics is slow, and it is being greatly outpaced by the development of bacterial resistance. This disparity places us in an increasingly vulnerable position because we are running out of safe and effective therapeutic options to treat antibiotic-resistant infections. This is exemplified by the emergence and persistence of hospital-acquired and community-associated methicillin-resistant S. aureus (MRSA), which has markedly narrowed our options for treating life-threatening staph infections. Thus, there is an urgent need to develop novel, potent, preventive, and therapeutic agents. In our current study, we performed a whole-cell screening assay of synthetic libraries for antibacterial activity and identified a novel molecule, MZ-01. MZ-01 exhibited potent bactericidal activity against Gram-positive bacterial pathogens, including MRSA, Streptococcus pyogenes, and Streptococcus pneumoniae, at low concentrations. MZ-01 killed and lysed both the late exponential phase of an S. aureus population and bacteria inside mammalian cells. Furthermore, MZ-01 exhibited low cytotoxicity. These results indicate that MZ-01 is a promising scaffold to guide the development of novel, potent antibacterial agents against multidrug-resistant Gram-positive bacterial pathogens such as MRSA.